2011
DOI: 10.1093/chemse/bjr106
|View full text |Cite
|
Sign up to set email alerts
|

Water Restriction and Fluid Temperature Alter Preference for Water and Sucrose Solutions

Abstract: The role of diet temperature in ingestive behavior is poorly understood. We examined the importance of stimulus temperature and water-restriction state on the preference for and intake of water and sucrose. Using custom-designed equipment that allows us to monitor and maintain solution temperatures during testing (±0.1 °C), we conducted a series of 2-bottle preference tests (10 °C water vs. sucrose 10-40 °C) and brief access tests (10-40 °C water and sucrose). Water-restricted rats preferred cold water over an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 28 publications
2
21
0
Order By: Relevance
“…ranges tested in our study, though threshold detections were not studied (Kapatos & Gold, 1972;Deaux, 1973;Smith et al 2010;Torregrossa et al 2012). Human subjects either (1) have difficulty identifying small temperature changes when applied focally to the tongue (Niissalo et al 2003), or (2) show no difference in detection thresholds for increased vs. decreased temperatures (Granot & Nagler, 2005;Kalantzis et al 2007), or (3) are more sensitive to cooling than to warming (Green, 1984;Renton et al 2003).…”
Section: Pretreatment With Menthol Affects Oral Thermosensory Respomentioning
confidence: 83%
“…ranges tested in our study, though threshold detections were not studied (Kapatos & Gold, 1972;Deaux, 1973;Smith et al 2010;Torregrossa et al 2012). Human subjects either (1) have difficulty identifying small temperature changes when applied focally to the tongue (Niissalo et al 2003), or (2) show no difference in detection thresholds for increased vs. decreased temperatures (Granot & Nagler, 2005;Kalantzis et al 2007), or (3) are more sensitive to cooling than to warming (Green, 1984;Renton et al 2003).…”
Section: Pretreatment With Menthol Affects Oral Thermosensory Respomentioning
confidence: 83%
“…; Torregrossa et al . ). Human subjects either (1) have difficulty identifying small temperature changes when applied focally to the tongue (Niissalo et al .…”
Section: Discussionmentioning
confidence: 97%
“…A number of studies have demonstrated that, given a choice, rats will chose to drink sucrose‐enriched water compared with water alone (Hsiao & Chen, ; Galic & Persinger, ; Torregrossa et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…The energy content per gram of the high-fat diet was higher than that of the low-fat diet and therefore rats did not need to eat as much to satisfy their metabolic needs. A number of studies have demonstrated that, given a choice, rats will chose to drink sucrose-enriched water compared with water alone (Hsiao & Chen, 1995;Galic & Persinger, 2002;Torregrossa et al 2012).…”
Section: Discussionmentioning
confidence: 99%